Reproductive Biology and Fishery-Related Characteristics of the Malabar Grouper (Epinephelus malabaricus) Caught in the Coastal Waters of Mafia Island, Tanzania. (21st July 2013) - Gaspare, Lydia; Bryceson, Ian
Abstract : The reproductive biology and fishery-related characteristics of the Malabar grouper ( Epinephelus malabaricus ) (Bloch and Schneider, 1801) specimens were investigated. The size of females ranged from 25 to 113 cm total length (L T ), with 50% sexually mature at 79 cm L T, and the males (97 cm to 114 cm L T ) were larger than the females. Due to the sex ratios and size distribution of the sample, it appeared that the groupers change sex between 97 and 113 cm L T . However, the gonadal histology data lacked specimens in the transitional stage. The spawning peak occurred in November, as defined by the presence of ripe females, and the spawning season lasted from September to February. The size of the fish correlated positively with the water depth at capture, which is also related to oxygen levels in deep water being more favourable for larger fish. Larger specimens (>100 cm L T ) were targeted by fishers between December and February, when the northeast monsoon coincides with calmer weather and the spawning season. Fishers were interviewed, and observations were made on fishing gear, vessels, and grounds. There was no indication that small-scale fishers targeted spawning aggregations; therefore, fisheries independent research is recommended in order to verify the time, location, and behaviour of the spawning of Malabar groupers for management and conservation purposes.